IMPLEMENTASI PEMBINAAN NARAPIDANA DI RUMAH TAHANAN NEGARA KELAS IIB SAMBAS - Amirul Arifin; Hasiah; Zainal Amaluddin (JOURNAL OF LAW AND NATION, 2025)
Law Number 22 of 2022 concerning Corrections emphasizes that inmate development is not limited to correctional institutions but can also be implemented in state detention centers. However, the implementation of correctional facilities at the Sambas Class IIB State Detention Center still faces various challenges, such as overcapacity, limited facilities, and a lack of structured rehabilitation programs. These conditions result in low rehabilitation effectiveness and a high inmate population. Therefore, this study aims to examine the implementation of inmate development at the Sambas Class IIB Detention Center from the perspective of Law Number 22 of 2022 concerning Corrections. The formulation of the problem in this study is: How is the implementation of Article 4 of Law Number 22 of 2022 concerning Corrections regarding the development of prisoners at the Sambas Class II B State Detention Center and what factors influence the development of prisoners at the Sambas Class II B State Detention Center. This research uses a qualitative method, a type of field research, namely research in the field aimed at obtaining information and describing events that occur in the field according to the facts found in the field, with an empirical juridical approach. Based on the research results and discussion above, the results indicate that the implementation of Article 4 of Law Number 22 of 2022 concerning Corrections at the Sambas Class IIB State Detention Center has been carried out, prioritizing the function of personality development and independence. Despite limited resources, implementation remains persuasive and collaborative. Factors such as overcrowding, understaffing, inadequate facilities, poor legal outreach, and the background of the inmates also influence the effectiveness of the rehabilitation.